Three-phase bridgeless boost PFC converter with variable duty cycle control - Morais, Douglas C. [UNESP]; De Seixas, Falcondes J. M. [UNESP]; E Silva, Luciano S. C.; João, C. P. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
The boost bridgeless converters operating in discontinuous-conduction-mode can offer both stages, rectification and elevation of voltage in high frequency, also can offer better efficiency when compared to the traditional single-switch one. Some these advantages are inherent to the converter operating mode, as the zero-current-switching during the turn-on of the switches, the simplicity of control system and the lower cost. However, the discontinuous-conduction-mode operation with constant duty cycle control leads to a high harmonic content of current in low frequency, limiting the converters applications by exceeding the limits imposed by international standards, for example by exceeding the harmonics requirement presented in IEC 61000-3-2. This paper presents the analysis and simulation of the three-phase bridgeless boost converter with variable duty cycle control. The principle of operation of the proposed converter is detailed and results of simulation shown the increase of the power factor by reducing the harmonic distortion of the input current.
Keywords: Discontinuous-conduction-mode; Power-factor-correction; Pulse-Width-Modulation; Three-phase bridgeless boost converter; Variable duty cycle control